2022
DOI: 10.3390/pathogens11020206
|View full text |Cite
|
Sign up to set email alerts
|

Sporothrix spp. Biofilms Impact in the Zoonotic Transmission Route: Feline Claws Associated Biofilms, Itraconazole Tolerance, and Potential Repurposing for Miltefosine

Abstract: Sporotrichosis is the most prevalent subcutaneous mycosis globally, and it is typically caused by direct inoculation of the soil saprophytic fungus Sporothrix spp. into the patients’ skin. However, sporotrichosis has an important zoonotic transmission route between cats and humans in hot-spot endemic areas such as Brazil. Antifungal itraconazole is the first-line treatment; however, it is frequently associated with recurrence after withdrawal, mainly on cats. Biofilms are important resistance structures relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…43 Traumatic inoculation can occur through scratching because the retractability of the nails can retain the fungus. 11 Also, inoculation can occur by biting and self-cleaning (licking) because cats can contaminate the oral cavity with the fungus present in the exudate of ulcerative lesions. 4,44 In some cats, it was possible to identify sites with bite wounds, especially on the back and with multiple distributions in the body, including the scrotum, raising the possibility of self-spread, as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…43 Traumatic inoculation can occur through scratching because the retractability of the nails can retain the fungus. 11 Also, inoculation can occur by biting and self-cleaning (licking) because cats can contaminate the oral cavity with the fungus present in the exudate of ulcerative lesions. 4,44 In some cats, it was possible to identify sites with bite wounds, especially on the back and with multiple distributions in the body, including the scrotum, raising the possibility of self-spread, as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of S. brasiliensis and S. schenckii to form biofilms on pieces of cat's claw has been evaluated. Both species showed different growth kinetics during the biofilm formation, and S. schenckii had higher metabolic activity during the first incubation time [41]. It was observed that S. schenckii and S. brasiliensis have different susceptibility profiles to antifungal drugs, the former being more susceptible in vitro than S. brasiliensis.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…In addition, it was recently shown that MFS has in vitro fungicidal activity against Sporothrix spp., inhibiting the growth of the mycelial phase of S. brasiliensis , S. schenckii , and Sporothrix globosa (45), and the yeast phase of S. brasiliensis strains resistant to (ITZ) and AMB (46). It was also demonstrated that alone or in combination with potassium iodide, MFS inhibits the biofilm formation of S. brasiliensis , S. schenckii , and S. globosa (47, 48). All of this evidence suggests the potential of MFS for treating sporotrichosis.…”
Section: Introductionmentioning
confidence: 99%